The Influence of Ethnocentrism Towards the Character Tolerance of the Children 4 - 6 Years Old in TK Kuncup Melati Semarang - Hardani, Avis Puspita; Windiarti, Rina (BELIA: Early Childhood Education Papers, 2016)
The attitude of ethnocentrism are often seen, especially in a multicultural environment like in TK Kuncup Melati Semarang. Therefore, it is very necessary to   instill tolerances character children at the kindergarten. This study aims to determine the effect of ethnocentrism on the development of the character of tolerance in children aged 4-6 years old in TK Kuncup Melati Semarang. This research uses descriptive statistics quantitative research. The sampling uses saturation sampling conducted in TK Kuncup Melati Semarang. The test results showed that Fcount F = 12.901 and t test results showed that t count = 3.592 with significance 0.001 < 0.05 means Ha is accepted which means no influence on the character of tolerance ethnocentrism children aged 4-6 years old in TK Kuncup Melati Semarang. While the results show the value of the coefficient of determination R Square = 0.212, which means ethnocentrism affect the character of tolerance of 21.2%. These results indicate that the effect on the character of tolerance ethnocentrism children aged 4-6 years old in TK Kuncup Melati Semarang is equal to 21.2%.